2010
DOI: 10.5638/thagis.18.117
|View full text |Cite
|
Sign up to set email alerts
|

An integrated approach to evaluate potential impact of precipitation and land-use change on streamflow in Srepok River Basin

Abstract: To manage water resources effectively at a local level, decision makers need to understand how climate change and human activity may impact local streamflow as a precious natural source of water use. However, the impact is often not well studied with locally obtained data such as monitored flow. This paper presents an integrated approach to study potential impact of precipitation and land-cover change on local streamflow over the next decades. The study area is the Srepok River basin, a tributary sub-basin of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Despite increasing precipitation, an increase in water demand, mainly agricultural water demand due to population increase, has a higher effect on the stream flow since there would be increased abstractions from the river. The findings were consistent with those obtained by Kawasaki et al (2010), who reported that population growth and land development had a greater impact on streamflow change than precipitation in the 50 years studied.…”
Section: Long-term Impact Scenario Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…Despite increasing precipitation, an increase in water demand, mainly agricultural water demand due to population increase, has a higher effect on the stream flow since there would be increased abstractions from the river. The findings were consistent with those obtained by Kawasaki et al (2010), who reported that population growth and land development had a greater impact on streamflow change than precipitation in the 50 years studied.…”
Section: Long-term Impact Scenario Analysissupporting
confidence: 92%
“…The climate data used in this study was downloaded from the Water Weather Energy Ecosystem website (www.2w2e.com) at a 0.5⁰ spatial resolution for the coordinates range of latitude −1⁰ to 0⁰ south, and longitude 37⁰ to 38⁰ east. Global climate data are generally more reliable for temperature than precipitation prediction; however, ensemble approaches could reduce these uncertainties (Kawasaki et al, 2010). The ensemble of the climate model projections shows an average annual temperature rise of 0.4 °C in 2030 and 1.4 °C in 2060; and a projected average annual precipitation increase of 2.2% by 2030 and 5.7% by 2060 with higher increases in March (4.1% and 12.5%) and October (9.4% and 18.2%) in the two periods.…”
Section: Long-term Streamflow Response To Land Use and Climate Changesmentioning
confidence: 99%
“…Most analyses of climate change impacts on river discharge in Vietnam have, to date, mainly focused on climate projection forcing from individual GCM or ensemble of GCMs. For example, Kawasaki et al (2010) used HEC-HMS model feeding from climate projections from Japanese Meteorological Agency GCM for the SRES A1B scenario to assess the climate changes impacts on water resources in Srepok watershed. Thai & Thuc (2011) employed MIKE 11 -NAM hydrological model and climate change scenarios of MONRE (2009), downscaled by MAGICC/SCENGEN and PRECIS model from GCMs to evaluate the impacts of climate change on the flow in Hong -Thai Binh and Dong Nai river basins.…”
Section: Introductionmentioning
confidence: 99%
“…Across dierent regions and times of the year, water resources are not evenly distributed (see [12]). Characterized by water-related development pressures and cross-boundary problems, increasing attention has been recently paid to Vietnam, particularly where there are limited ground monitoring stations (Kawasaki et al [4], Tran et al [7,8]; Vu et al [9]).…”
Section: Introductionmentioning
confidence: 99%